Simulation and optimization of tuneable microstrip patch antenna for fifth-generation applications based on graphene - Hamzah M. Marhoon; Nidal Qasem (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Microstrip patch antennas (MPAs) are known largely for their versatility in terms of feasible geometries, making them applicable in many distinct circumstances. In this paper, a graphene-based tuneable single/array rectangular microstrip patch antenna (MPA) utilizing an inset feed technique designed to function in multiple frequency bands are used in a fifth-generation (5G) wireless communications system. The tuneable antenna is used to eliminate the difficulties caused by the narrow bandwidths typically associated with MPAs. The graphene material has a reconfigurable surface conductivity that can be adjusted to function at the required value, thus allowing the required resonance frequency to be selected. The simulated tuneable antenna comprises a copper radiating patch with four graphene strips used for tuning purposes and is designed to cover a wide frequency band. The proposed antenna can be tuned directly by applying a direct current (DC) voltage to the graphene strips, resulting in a variation in the surface impedance of the graphene strips and leading to shifts in the resonance frequency.